HUBUNGAN ANTARA TINGKAT AKTUALISASI DIRI DENGAN KEBERMAKNAAN HIDUP PADA PRIA HOMOSEKSUAL - Nia H. Septiani (Psympathic : Jurnal Ilmiah Psikologi, 2011)
This research specifically observes the correlation between self actualization level and life meaning of homosexual men in a Bandung association. This research has been done because condition of society who has not been able to accept the existing of homosexual men in the association, many probles must be faced by them which enables to disturb their actualization with assumption that it relates to their life meaning. The design used in this research is non experimental design and correlation method. The research data are taken from the measurement tool encompassing self actualization data based on theory concept said by Maslow (1984). Whereas, the measurement tool used to get the date of the life meaning composed by James Crumbaugh dan Leonard Maholick  (Frankl, 1984) named The Purpose in Life Test. The result of analysis shows that correlative coefficient of both variables is 0.685 with Pv = 0,000 on significant standard α= 0,05 by two side tests. Basing on the result of significant test, it is known that thitung = 4,98. The result of data analysis shows that correlative coefficient of both variables is 0.685 with Pv = 0,000 on significant standard α= 0,05 by two side tests.basing on the result of significant test, it is known that thitung = 4,98. With standard significance α=0,05 and (dkn-2) =28 for two side test, it is know that ttabel = 2.048. These results show that there is significant positive correlation between self actualization and life meaning.